Kajian Yuridis Tindak Pidana Kekerasan Dalam Rumah Tangga - Asri Alawqiah; Muh. Darwis (Jurnal Litigasi Amsir, 2023)
This research was conducted with the aim of knowing the forms of domestic violence regulated in Law Number 23 of 2004 concerning Domestic Violence. And to find out the factors behind the occurrence of domestic violence in Parepare City in Parepare City throughout 2021-2022. The type of research used in this study is the type of research used in this research is normative and empirical research or commonly known as legal research which combines the two. The results of the research show that the form of Domestic Violence is caused by the occurrence of domestic violence starting from fights and also conflicts that occur as a result of differences of opinion and also debates that lead to violence both in the form of physical violence, namely beatings, kicks, and also encouragement made by husbands to wives and also psychological violence that is carried out by saying words that should not be appropriate to say to a wife. These words can be in the form of dirty words, swearing, and also speak using a high tone and it is more appropriate to say it by shouting at the wife. As well as the factors behind the occurrence of domestic violence in Parepare City are individual factors, namely often drunk because of alcoholic beverages, those who grew up in difficult circumstances, perpetrators not used to controlling their anger, perpetrators have difficulty expressing feelings through words, people who experience pressure or stress due to work and not being able to deal with family matters as well as family factors which include chaotic family life, not loving and respecting each other, and not appreciating the role of women, lack of familiarity and social network relationships in the family, the nature of nuclear family life not the extended family. and Community factors consisting of poverty, urbanization that occurs accompanied by an income gap between residents, an environment with a high frequency of violence and crime to testify as a witness, namely about matters entrusted to them